Surface protective sheet

By using an adhesive layer of aqueous dispersed acrylate polymer and other additives in the surface protection sheet and combining a support substrate of a low-polar material, the problems of insufficient adhesion and high contamination risk in the metal plate treatment process in the prior art are solved, and stronger adhesion and lower contamination risk are achieved.

JP2025068641APending Publication Date: 2025-04-30NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023178540
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

The existing surface protective sheets are difficult to meet the dual requirements of strength and non-contamination during metal plate treatment, especially when heat treatment is performed, which can easily lead to the transfer and contamination of adhesives.

Method used

Adhesive layers containing aqueous dispersed acrylate polymers, aqueous dispersed acrylic acid ester polymers, aqueous dispersed accretions, leveling agents and crosslinking agents are used, and the composition ratio of the adhesive layer is adjusted to improve adhesion and reduce the risk of contamination.

Benefits of technology

It achieves stronger adhesive force and lower pollution risk during metal plate treatment, and is not likely to cause adhesion transfer during heat treatment, improving manufacturing efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025068641000001_ABST
    Figure 2025068641000001_ABST
Patent Text Reader

Abstract

To provide a surface protective sheet having an adhesive layer formed from a water dispersion type adhesive composition including an acrylic polymer, low staining to an adherend while exhibiting an adhesive strength stronger than that of a prior surface protective sheet, and excellent in appearance quality.SOLUTION: A surface protective sheet includes: an adhesive layer; and a support base material for supporting the adhesive layer on a first surface. The adhesive layer is formed from a water dispersion type adhesive composition including an acrylic polymer, a water dispersion type tackifier, a leveling agent, and a cross-linking agent. The content of the water dispersion type tackifier is 5 pts.wt. or more and 40 pts.wt. or less to 100 pts.wt. of the acrylic polymer, and the content of the leveling agent is 0.3 pts.wt. or more and 3 pts.wt. or less to 100 pts.wt. of the acrylic polymer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface protection sheet. [Background technology]

[0002] Generally, adhesives (also called pressure-sensitive adhesives; the same applies below) are in a soft solid (viscoelastic) state in a temperature range around room temperature, and have the property of easily adhering to an adherend by pressure. Taking advantage of such properties, adhesives are widely used for various purposes in the form of a single-sided adhesive sheet with a substrate, in which an adhesive layer is provided on one surface of the substrate. For example, the single-sided adhesive sheet with a substrate is attached to a metal plate and is preferably used as a surface protection sheet that protects the surface of the metal plate during drawing, bending, punching, etc. of the metal plate. Patent Document 1 can be cited as a technical document relating to adhesives or adhesive sheets for surface protection. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-16677 A Summary of the Invention [Problem to be solved by the invention]

[0004] After the protective purpose is achieved, the surface protective sheet is removed from the adherend at an appropriate time. Therefore, for example, a surface protective sheet for metal plate processing is required to have a property that allows the surface protective sheet to be easily peeled off from the metal plate (work) after processing. On the other hand, for example, a surface protective sheet for metal plate processing is required to have an adhesive strength that does not cause problems such as lifting or peeling off from the adherend metal plate during processing of the metal plate. In particular, a surface protective sheet for metal plate processing in which pressure is applied to plastically deform the metal three-dimensionally, such as press processing (typically drawing), is required to have an adhesive strength stronger than that of conventional surface protective sheets in order to suppress the occurrence of lifting or peeling.

[0005] In addition, the surface protection sheet is required to have a property of not contaminating the adherend to be protected. In general, the adhesive tends to increase its adhesive strength or migrate components derived from the adhesive when heated, which promotes the deterioration of the contaminating property of the adherend. Therefore, it is particularly advantageous if a surface protection sheet that is less likely to contaminate the adherend even if the surface protection sheet is heated while attached to the adherend to be protected is realized. If a surface protection sheet that has a stronger adhesive strength than a conventional surface protection sheet and shows low contamination even when subjected to heat treatment is realized, it can be used to consistently protect the surface of the adherend in a series of manufacturing processes for molded bodies, including press processing of a metal plate, resin injection into the press processed product, and heat treatment, without having to replace the work of replacing the surface protection sheet with a new one in the middle of the manufacturing process, which is preferable from the viewpoint of manufacturing efficiency.

[0006] Incidentally, a water-dispersed adhesive composition having an acrylic polymer as a base polymer is preferable from the viewpoint of reducing the environmental load because it uses water as a dispersion medium for the adhesive component, and is also advantageous from the viewpoint of reducing the amount of volatile organic compounds (VOCs) emitted from an adhesive layer formed using the composition. However, when a tackifier is added to the water-dispersed adhesive composition for the purpose of improving adhesion, when the water-dispersed adhesive composition is applied to form an adhesive layer, repelling may easily occur in the coating film of the composition. Repelling of the coating film is reflected in the shape of the adhesive layer obtained after drying, and causes appearance defects such as dents in the adhesive layer (or loss of the adhesive layer in severe cases).

[0007] The present invention has been created in consideration of the above circumstances, and has as its main object to provide a surface protection sheet which has an adhesive layer formed from a water-dispersible adhesive composition containing an acrylic polymer, and which exhibits stronger adhesive strength than conventional surface protection sheets while being less contaminating to an adherend and having excellent appearance quality. [Means for solving the problem]

[0008] The surface protection sheet provided by this specification includes a pressure-sensitive adhesive layer formed from a water-dispersed pressure-sensitive adhesive composition containing an acrylic polymer, a water-dispersed tackifier, a leveling agent, and a crosslinking agent, and a support substrate in the form of a sheet having a first surface and a second surface, which supports the pressure-sensitive adhesive layer on the first surface. Here, the content of the water-dispersed tackifier is 5 parts by weight or more and 40 parts by weight or less relative to 100 parts by weight of the acrylic polymer, and the content of the leveling agent is 0.3 parts by weight or more and 3 parts by weight or less relative to 100 parts by weight of the acrylic polymer. The surface protection sheet having such a configuration is likely to have improved adhesive strength due to the effect of the water-dispersed tackifier, and can suppress an increase in cissing caused by adding the water-dispersed tackifier due to the effect of the leveling agent, and can have excellent appearance quality. In addition, since the contents of the water-dispersed tackifier and the leveling agent are each limited to a specific range, the sheet is likely to exhibit low contamination of the adherend.

[0009] In some preferred embodiments, at least the first surface of the support substrate is made of a polyolefin resin. According to the technology disclosed herein, the adhesive strength is improved while the occurrence of cissing of the water-dispersed pressure-sensitive adhesive composition is suppressed. For this reason, it is particularly meaningful to apply the technology disclosed herein to a substrate whose surface is made of a low-polarity material such as a polyolefin resin, which is prone to cissing of the water-dispersed pressure-sensitive adhesive composition. In some embodiments, the support substrate is a single-layer support substrate made of a polyolefin resin film.

[0010] In some preferred embodiments, the surface protection sheet has a peel strength (adhesive strength) S measured at a tensile speed of 10 mm / min and a peel angle of 180 degrees against a stainless steel plate. A The peel strength S is measured by peeling at a tensile speed of 10 mm / min, which is slower than the usual measurement conditions. A A surface protection sheet having a hardness within the above range is less likely to peel off or float from the adherend, even when used to protect the surface of a metal plate during metal plate processing such as press working.

[0011] In some preferred embodiments, the thickness of the surface protection sheet is greater than 20 μm and not greater than 100 μm. A surface protection sheet having such a thickness is preferred from the standpoints of handleability, strength, protection, etc.

[0012] In some preferred embodiments, the thickness of the pressure-sensitive adhesive layer is 2 μm or more and 20 μm or less. When the thickness of the pressure-sensitive adhesive layer is equal to or more than the lower limit, the adhesion to the adherend surface is easily improved. When the thickness of the pressure-sensitive adhesive layer is equal to or less than the upper limit, the excessive increase in adhesive strength is easily suppressed and the staining property is easily reduced.

[0013] According to this specification, a method for producing a surface protective sheet is provided. The method includes preparing a water-dispersed pressure-sensitive adhesive composition containing an acrylic polymer, a water-dispersed tackifier, a leveling agent, and a crosslinking agent, and directly applying the water-dispersed pressure-sensitive adhesive composition to the first surface of a sheet-shaped support substrate having a first surface and a second surface to form a pressure-sensitive adhesive layer. Here, the water-dispersed pressure-sensitive adhesive composition contains 5 parts by weight or more and 40 parts by weight or less of the water-dispersed tackifier and 0.3 parts by weight or more and 3 parts by weight or less of the leveling agent relative to 100 parts by weight of the acrylic polymer. The pressure-sensitive adhesive layer formed by the water-dispersed pressure-sensitive adhesive composition having such a configuration is likely to have improved adhesive strength due to the effect of the water-dispersed tackifier, and can suppress an increase in repelling caused by adding the water-dispersed tackifier due to the effect of the leveling agent, and can have excellent appearance quality. In addition, since the contents of the water-dispersed tackifier and the leveling agent are limited to a predetermined range, the pressure-sensitive adhesive layer is likely to exhibit low contamination to the adherend. When such a water-dispersible pressure-sensitive adhesive composition is applied directly to the first surface of a supporting substrate to form a pressure-sensitive adhesive layer, a surface protection sheet that exhibits stronger adhesion than conventional surface protection sheets, while having low staining properties toward the adherend and excellent appearance quality is easily obtained. [Brief description of the drawings]

[0014] [Figure 1]FIG. 1 is a schematic cross-sectional view showing a surface protection sheet according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Preferred embodiments of the present invention will be described below. Matters necessary for carrying out the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on carrying out the invention described in this specification and the common general technical knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general technical knowledge in the relevant field.

[0016] In this specification, "(meth)acryloyl" refers collectively to acryloyl and methacryloyl. Similarly, "(meth)acrylate" refers collectively to acrylate and methacrylate, and "(meth)acrylic" refers collectively to acrylic and methacrylic.

[0017] In this specification, the term "acrylic monomer" refers to a monomer having at least one (meth)acryloyl group in one molecule. In addition, in this specification, the term "acrylic polymer" refers to a polymer containing a monomer unit derived from an acrylic monomer. A typical example of an acrylic polymer is a polymer in which 50% by weight or more of the monomers (total monomer components) corresponding to the composition of the acrylic polymer are acrylic monomers.

[0018] The surface protection sheet disclosed herein has a sheet-shaped support substrate having a first surface and a second surface, and an adhesive layer supported on the first surface of the support substrate. The cross-sectional structure of a surface protection sheet according to an embodiment is shown in FIG. 1. This surface protection sheet 10 has a configuration in which an adhesive layer 2 is provided on a first surface (front surface) 1A of a support substrate 1, and is used by attaching a surface (adhesive surface) 2A of the adhesive layer 2 to an object to be protected. The surface protection sheet 10 before use (i.e., before attachment to an object to be protected) may be in a form in which the adhesive surface 2A is protected by a release liner (not shown) in which at least the adhesive layer side is a release surface. Alternatively, the surface protection sheet 10 may be in a form in which the second surface (back surface) 1B of the support substrate 1 is a release surface, and the surface protection sheet 10 is wound into a roll so that the adhesive layer 2 abuts against the other surface to protect the adhesive surface 2A.

[0019] The release liner can be any conventional release paper, and is not particularly limited. For example, a release liner having a release treatment layer on the surface of a liner substrate such as a plastic film or paper, or a release liner made of a low-adhesion material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin-based resin, can be used. The release treatment layer can be formed by surface-treating the liner substrate with various release treatment agents such as silicone-based, long-chain alkyl-based, fluorine-based, and molybdenum sulfide.

[0020] <Supporting base material> The supporting substrate of the surface protection sheet disclosed herein is not particularly limited as long as it is a sheet-shaped substrate capable of supporting an adhesive layer on the first surface. For example, a resin film, paper, cloth, rubber sheet, foam sheet, metal foil, a composite of these, etc. can be used as the supporting substrate. Examples of paper include Japanese paper, craft paper, glassine paper, wood-free paper, synthetic paper, topcoat paper, etc. Examples of cloth include woven fabrics and nonwoven fabrics made by spinning various fibrous materials alone or in combination. Examples of the fibrous materials include cotton, staple fiber, Manila hemp, pulp, rayon, acetate fiber, polyester fiber, polyvinyl alcohol fiber, polyamide fiber, polyolefin fiber, etc. Examples of rubber sheets include natural rubber sheets and butyl rubber sheets. Examples of foam sheets include foamed polyurethane sheets and foamed polychloroprene rubber sheets. Examples of metal foils include aluminum foil and copper foil.

[0021] The technology disclosed herein can be preferably applied to a surface protection sheet having a resin film as a supporting substrate. The "resin film" referred to here is typically a film formed by forming a resin composition mainly composed of the following resin components into a film, and is a concept that is distinguished from so-called nonwoven fabrics and woven fabrics (i.e., a concept that excludes nonwoven fabrics and woven fabrics). A substantially non-foamed resin film is preferred. Here, the non-foamed resin film refers to a resin film that has not been intentionally treated to form a foam, and specifically, it may be a resin film with an expansion ratio of approximately less than 1.1 times (for example, less than 1.05 times, typically less than 1.01 times).

[0022] Examples of resin components constituting the resin film include polyolefin resins (polyethylene (PE), polypropylene (PP), ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, etc.), vinyl chloride resins (typically soft vinyl chloride resins), vinyl acetate resins, polyurethane resins (ether-based polyurethanes, ester-based polyurethanes, carbonate-based polyurethanes, etc.), urethane (meth)acrylates, thermoplastic elastomers (olefin-based elastomers, styrene-based elastomers, acrylic elastomers, etc.), polyester-based resins (polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, etc.), polycarbonate resins, polyamide resins, polyimide resins, fluorine-based resins, cellulose-based resins such as cellophane resins, etc. These may be used alone or in combination of two or more.

[0023] Although not particularly limited, in the surface protection sheet according to one embodiment, a support substrate containing one or more resin components selected from the group consisting of polyolefin resins, vinyl chloride resins, polyurethane resins, and thermoplastic elastomers as the main component (typically, a support substrate containing more than 50% by weight of such resin components) can be preferably used. For example, a support substrate containing more than 50% by weight of any of these resins is preferred. Among the above resin materials, polyolefin resins, polyurethane resins, and olefin elastomers are preferred from the viewpoints of thermal stability, light weight, etc., and polyolefin resins and olefin elastomers are particularly preferred from the viewpoints of handling, etc.

[0024] The surface protection sheet disclosed herein can be preferably implemented in an embodiment in which the supporting substrate is made mainly of polyolefin resin (contains more than 50% by weight), i.e., a polyolefin resin film is used as the supporting substrate. For example, a polyolefin resin film in which 50% by weight or more of the entire supporting substrate is polyethylene (PE) resin or polypropylene (PP) resin can be preferably used. In other words, the polyolefin resin film can be one in which the total amount of PE resin and PP resin accounts for 50% by weight or more of the entire substrate.

[0025] The PP resin may be mainly composed of various polymers (propylene-based polymers) containing propylene as a constituent monomer. The PP resin may be substantially composed of one or more propylene-based polymers. The concept of propylene-based polymers here includes homopolypropylene, as well as random copolymers (random polypropylenes) and block copolymers (block polypropylenes) of propylene and other monomers. The concept of propylene-based polymers here includes, for example, the following: Homopolymers of propylene (homopolypropylene), e.g. isotactic polypropylene. A random copolymer (random polypropylene) of propylene and another α-olefin (typically, one or more selected from ethylene and α-olefins having 4 to 10 carbon atoms). Preferably, the random polypropylene has propylene as the main monomer (the main constituent monomer, i.e., a component that accounts for 50% by weight or more of the total monomers). A copolymer (block polypropylene) in which propylene is block-copolymerized with another α-olefin (typically, one or more selected from ethylene and α-olefins having 4 to 10 carbon atoms). Preferably, the block polypropylene has propylene as the main monomer (the main constituent monomer, i.e., a component that accounts for 50% by weight or more of the total monomers).

[0026] The PE resin may be mainly composed of various polymers (ethylene-based polymers) containing ethylene as a constituent monomer. The PE resin may be substantially composed of one or more ethylene-based polymers. The ethylene-based polymer may be a homopolymer of ethylene, or may be a copolymer of ethylene as a main monomer and another α-olefin as a secondary monomer (random copolymerization, block copolymerization, etc.). Suitable examples of the α-olefin include α-olefins having 3 to 10 carbon atoms, such as propylene, 1-butene (which may be branched 1-butene), 1-hexene, 4-methyl-1-pentene, and 1-octene. For example, a PE resin mainly composed of an ethylene-based polymer copolymerized with the α-olefin as a secondary monomer at a ratio of 10% by weight or less (typically 5% by weight or less) may be preferably used.

[0027] The PE resin may also be a PE resin containing a copolymer of ethylene and a monomer (functional group-containing monomer) having another functional group in addition to the polymerizable functional group, or a PE resin in which such a functional group-containing monomer is copolymerized with an ethylene-based polymer, etc. Examples of copolymers of ethylene and functional group-containing monomers include ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl methacrylate copolymer (EMMA), and ethylene-(meth)acrylic acid (i.e., acrylic acid and / or methacrylic acid) copolymers crosslinked with metal ions.

[0028] The density of the PE resin is not particularly limited. The concept of PE resin here includes high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE) and linear low density polyethylene (LLDPE). In one embodiment, the density of the PE resin is, for example, 0.90 to 0.94 g / cm 3The PE resin may be about 100%. Preferred PE resins include LDPE and LLDPE. The PE resin may contain one or more types of LDPE and one or more types of LLDPE. The blend ratio of each LDPE or LLDPE, or the blend ratio of LDPE and LLDPE is not particularly limited, and can be appropriately set to obtain a PE resin exhibiting desired properties. A laminated resin film containing such a polyethylene resin film as a component may be used.

[0029] The support substrate may have a single layer structure, or a multi-layer structure of two, three or more layers. In the case of a multi-layer structure, at least one layer (preferably all layers) is preferably any of the above-mentioned resin films. For example, the support substrate is preferably configured such that 75% or more (more preferably 90% or more) of the thickness is made of a single-layer or multi-layer (typically single-layer) polyolefin resin film. The support substrate may be entirely made of a single-layer or multi-layer polyolefin resin film.

[0030] The technology disclosed herein can be preferably implemented in the form of a surface protection sheet in which at least the first surface (i.e., the surface portion adjacent to the pressure-sensitive adhesive layer; hereinafter, also referred to as the "front surface") of the support substrate is made of a polyolefin resin. A single-layer support substrate made of any of the polyolefin resin films (PE resin film, PP resin film, etc.) disclosed herein is a typical example of a support substrate having a first surface made of a polyolefin resin. Another example of a support substrate having a first surface made of a polyolefin resin is a multilayer support substrate in which a polyolefin resin layer is disposed at least on the front surface. The support substrate may be a multilayer support substrate having a plurality of layers formed of a polyolefin resin, the layers being disposed on the front surface and other portions (e.g., the second surface, i.e., the back surface). The first surface made of a polyolefin resin has low polarity, so that cissing is likely to occur in the aqueous dispersion-type pressure-sensitive adhesive composition coated on the first surface. Therefore, it is particularly meaningful to realize low cissing by applying the technology disclosed herein.

[0031] The resin film (e.g., polyolefin resin film) used as the supporting substrate of the surface protection sheet disclosed herein may contain appropriate components that are permitted to be contained in the supporting substrate as necessary. For example, additives such as fillers (inorganic fillers, organic fillers, etc.), colorants (pigments, dyes), antioxidants, light stabilizers (meaning including radical scavengers, ultraviolet absorbers, etc.), antistatic agents, plasticizers, slip agents, and antiblocking agents can be appropriately blended. The blending amount of each additive can be, for example, about the same as the usual blending amount in the field of resin films used as supporting substrates of surface protection sheets, etc.

[0032] In a preferred embodiment, the support substrate is transparent (including translucent). In a surface protection sheet having such a support substrate, if there is an appearance defect (e.g., air bubbles) in the pressure-sensitive adhesive layer, the appearance defect is easily seen from the back side of the surface protection sheet through the support substrate, and the appearance quality is easily impaired. According to the technology disclosed herein, the appearance defect of the pressure-sensitive adhesive layer is prevented, so that excellent appearance quality can be obtained even in a configuration having a transparent support substrate. Here, the support substrate being transparent means that the support substrate exhibits a total light transmittance of 50% or more. In addition, the haze value of the support substrate is preferably 30% or less (e.g., 20% or less). The total light transmittance and haze value can be measured using a commercially available transmittance meter in accordance with JIS K 7136:2000.

[0033] The manufacturing method of the support substrate is not particularly limited, and may be appropriately adopted from a conventionally known method.For example, when a resin film is used as the support substrate, a resin film produced by appropriately adopting a conventionally known general film forming method such as inflation molding, extrusion molding, T-die casting molding, and calendar roll molding can be used.

[0034] The thickness of the support substrate is not particularly limited, but from the viewpoint of the strength and protectiveness of the surface protective sheet, it is usually appropriate to be about 10 μm or more, preferably about 20 μm or more, and may be about 30 μm or more (for example, about 40 μm or more). In addition, the thickness of the support substrate can be, for example, about 200 μm or less, and from the viewpoint of the flexibility and handling of the surface protective sheet, it is usually appropriate to be about 150 μm or less, preferably about 100 μm or less, and may be about 75 μm or less (for example, about 60 μm or less).

[0035] The first surface of the support substrate may be subjected to a conventionally known surface treatment such as corona discharge treatment, plasma treatment, ozone exposure, flame exposure, ultraviolet irradiation treatment, acid treatment, alkali treatment, application of a primer, etc. Such a surface treatment may be a treatment for improving the adhesion between the support substrate and the pressure-sensitive adhesive layer, in other words, the anchoring property of the pressure-sensitive adhesive layer to the substrate. In a support substrate in an embodiment in which the first surface is the surface of a resin film (particularly, an embodiment in which the first surface is composed of a polyolefin resin), it is particularly meaningful to perform such a surface treatment.

[0036] <Adhesive layer> The surface protection sheet disclosed herein comprises a pressure-sensitive adhesive layer formed from a water-dispersed pressure-sensitive adhesive composition on a first surface of the support substrate as described above. The water-dispersed pressure-sensitive adhesive composition includes an acrylic polymer, a water-dispersed tackifier, a leveling agent, and a crosslinking agent.

[0037] (Acrylic polymer) In some preferred embodiments, the acrylic polymer in the technology disclosed herein is an alkyl acrylate having an alkyl group with 4 to 9 carbon atoms (hereinafter, monomer m A It is a polymer of a monomer raw material containing the above-mentioned acrylic polymer and may contain other monomers as necessary. The acrylic polymer can be synthesized by polymerizing a monomer raw material of the corresponding composition (monomer composition) by a known method. As the polymerization method, an emulsion polymerization method can be preferably adopted.

[0038] Monomer m ANon-limiting examples of monomer m include n-butyl acrylate (BA), n-hexyl acrylate, 2-ethylhexyl acrylate (2EHA), n-octyl acrylate, n-nonyl acrylate, and isononyl acrylate (iNA). Preferred are alkyl acrylates containing a -(CH2)3- structure in the alkyl group, and more preferred are alkyl acrylates containing a -(CH2)4- structure in the alkyl group. A Suitable examples of monomer m include 2EHA, BA and iNA. A can be used alone or in combination of two or more.

[0039] Monomer m A The amount of monomer m used is typically 40% by weight or more of the total monomer raw materials used in the synthesis of an acrylic polymer. A The inclusion of 40% by weight or more of the monomer m is advantageous in terms of improving the flexibility and low-temperature properties of the pressure-sensitive adhesive layer containing the acrylic polymer. A The proportion of the monomer m in the monomer composition is preferably 45% by weight or more, and may be 50% by weight or more (for example, more than 50% by weight). A By making the proportion of the monomer m 99.9% by weight or less, it becomes easier to impart appropriate cohesiveness to the pressure-sensitive adhesive layer containing the acrylic polymer. A The proportion of the monomer m is preferably 95% by weight or less, more preferably 90% by weight or less, and may be 85% by weight or less. A The proportion may be less than 80% by weight, or less than 70% by weight (for example, 65% by weight or less).

[0040] The acrylic polymer in the technology disclosed herein is a carboxyl group-containing monomer (hereinafter, monomer m B That is, the acrylic polymer may have a monomer composition containing the monomer m B may be copolymerized. BMonomer m can be useful for introducing crosslinking points into the acrylic polymer and for increasing the cohesive strength of the pressure-sensitive adhesive layer containing the acrylic polymer. B can also be useful for improving non-adhesive residue by increasing the adhesion (anchoring property) between the adhesive layer containing the acrylic polymer and the supporting substrate. Examples of carboxyl group-containing monomers include ethylenically unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, isocrotonic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, and 1-[2-(methacryloyloxy)ethyl]succinic acid; ethylenically unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid, and their anhydrides (e.g., maleic anhydride, itaconic anhydride); and the like. The carboxyl group-containing monomers can be used alone or in combination of two or more.

[0041] Monomer m B When using the monomer m B The ratio of monomer m is not particularly limited. B The proportion of the monomer m can be, for example, 0.05% by weight or more, and is usually 0.1% by weight or more. From the viewpoint of polymerization stability and dispersion stability, the proportion is preferably 0.5% by weight or more, and more preferably 1% by weight or more. In addition, from the viewpoint of suppressing an excessive increase in peel strength (adhesive strength), the proportion of the monomer m B The proportion of is usually 5% by weight or less, preferably 4% by weight or less (for example, 3% by weight or less).

[0042] The acrylic polymer in the technology disclosed herein contains an alkyl (meth)acrylate (hereinafter, referred to as monomer m) having an alkyl group with 4 to 20 carbon atoms and a homopolymer Tg of −50° C. or higher for the purpose of adjusting the glass transition temperature (Tg) of the acrylic polymer. C Here, the above-mentioned monomer m may be copolymerized. A The monomers belonging to the group are monomers m C Monomer m is excluded from the category. C Monomer m may be used alone or in combination of two or more.C The Tg of the homopolymer is preferably in the range of -40°C to +60°C, and more preferably in the range of -30°C to +40°C (for example, -20°C to +30°C). C Non-limiting examples include n-butyl methacrylate (BMA), 2-ethylhexyl methacrylate, and lauryl acrylate.

[0043] Monomer m C When using the monomer m C The ratio of monomer m is not particularly limited. C The proportion of the monomer m can be, for example, 1% by weight or more, may be 5% by weight or more, may be 10% by weight or more, or may be 15% by weight or more. C In order to more effectively exert the effect of the monomer m C The proportion of may be 20% by weight or more, 25% by weight or more, 30% by weight or more, or even 35% by weight or more (for example, 40% by weight or more).

[0044] The acrylic polymer in the technology disclosed herein may contain, as necessary, a monomer m A ~m C Monomers other than (monomer m D ) may be copolymerized. D As the monomer m A Various monomers copolymerizable with the above may be used singly or in combination of two or more.

[0045] Monomer m D Examples of the monomer include alkyl (meth)acrylates represented by the following general formula (1) (monomer m D1 ) (wherein monomer m A or monomer m C ) may be used. CH2=C(R 1 )COOR 2 (1) Here, R in the above general formula (1) 1 is a hydrogen atom or a methyl group. 2 is an alkyl group having 1 to 20 carbon atoms. Hereinafter, this range of carbon atoms will be referred to as "C 1-20 From the viewpoint of polymerization reactivity and emulsion polymerization stability, R 2 C 1-16 Preferred is an alkyl (meth)acrylate, where R 2 C 1-12 More preferred is an alkyl (meth)acrylate, which is an alkyl group of the above formula.

[0046] Monomer m D1 Specific examples of alkyl (meth)acrylates that can be used as monomer m include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, lauryl (meth)acrylate, tetradecyl (meth)acrylate, and hexadecyl (meth)acrylate. D1 can be used alone or in combination of two or more.

[0047] Monomer m D Examples of compounds that can be used as the functional group-containing monomer include the following: Such functional group-containing monomers can be useful for introducing crosslinking points into the acrylic polymer or for increasing the cohesive strength of the acrylic polymer. Hydroxyl group-containing monomers: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl acrylate; unsaturated alcohols such as vinyl alcohol and allyl alcohol. Amide group-containing monomers: for example, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, diacetone(meth)acrylamide. Imido group-containing monomers: for example, N-isopropylmaleimide, N-cyclohexylmaleimide, itaconimide. Amino group-containing monomers: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, t-butylaminoethyl (meth)acrylate. Monomers having an epoxy group: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, allyl glycidyl ether. Cyano group-containing monomers: for example acrylonitrile, methacrylonitrile. Keto group-containing monomers: for example, diacetone (meth)acrylamide, diacetone (meth)acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, vinyl acetoacetate. Monomers having a nitrogen atom-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, N-(meth)acryloylmorpholine, N-(meth)acryloylpyrrolidone. Alkoxysilyl group-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane.

[0048] Monomer m D Other examples of compounds that can be used as the ester monomer include vinyl ester monomers such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene, substituted styrenes (such as α-methylstyrene), and vinyl toluene; non-aromatic ring-containing (meth)acrylates such as cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, cyclopentyl di(meth)acrylate, and isobornyl (meth)acrylate; aryl (meth)acrylates (e.g., phenyl (meth)acrylate, benzyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), and the like. acrylate), aromatic ring-containing (meth)acrylates such as arylalkyl (meth)acrylates (for example, benzyl (meth)acrylate); olefin-based monomers such as ethylene, propylene, isoprene, butadiene, isobutylene, etc.; chlorine-containing monomers such as vinyl chloride, vinylidene chloride, etc.; isocyanate group-containing monomers such as 2-(meth)acryloxyethyl isocyanate, etc.; alkoxy group-containing monomers such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, etc.; vinyl ether-based monomers such as methyl vinyl ether, ethyl vinyl ether, isobutyl vinyl ether, etc.;

[0049] Monomer m D Further examples of compounds that can be used include polyfunctional monomers. Specific examples of polyfunctional monomers include compounds having two or more (meth)acryloyl groups in one molecule, such as 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and methylenebisacrylamide. When using such polyfunctional monomers, the amount used is not particularly limited, but it is usually appropriate to use 2% by weight or less (more preferably 1% by weight or less) of the total monomer components.

[0050] Monomer m DThe amount of monomer m used is usually set to not exceed 40% by weight, preferably not exceeding 20% ​​by weight, and more preferably not exceeding 10% by weight of the monomer composition. D The technology disclosed herein does not require the use of monomer m D The amount of monomer m used is preferably 0% by weight or more and less than 5% by weight of the monomer composition. D The use amount of monomer m is 0% by weight of the monomer composition, which is at least intentionally D This means that you do not use

[0051] In a preferred embodiment of the technology disclosed herein, the ratio of the acrylic monomer to the total monomer components constituting the acrylic polymer can be more than 95% by weight and not more than 100% by weight. That is, an acrylic polymer having a copolymerization ratio of the acrylic monomer of more than 95% by weight is preferred. A pressure-sensitive adhesive composition having such an acrylic polymer as a base polymer can be advantageous in terms of the weather resistance of a pressure-sensitive adhesive layer formed from the composition (and thus a surface protection sheet having the pressure-sensitive adhesive layer).

[0052] Although not particularly limited, the acrylic polymer preferably has a copolymer composition that makes the Tg of the polymer -20°C or less. From the viewpoint of enhancing adhesion to the adherend, the Tg of the acrylic polymer is preferably -20°C or less, more preferably -25°C or less. In addition, from the viewpoint of suppressing an excessive increase in peel strength (adhesive strength), the Tg of the acrylic polymer is usually -60°C or more, more preferably -55°C or more. The Tg of the acrylic polymer can be adjusted by appropriately changing the monomer composition (i.e., the type and amount ratio of the monomers used in the synthesis of the polymer).

[0053] In this specification, the Tg of a polymer refers to a value calculated from the Fox formula based on the Tg of a homopolymer of each monomer constituting the polymer and the weight fraction (copolymerization ratio by weight) of the monomer. The Fox formula is a relational expression between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg=Σ(Wi / Tgi) In the above Fox formula, Tg represents the glass transition temperature (unit: K) of the copolymer, Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio on a weight basis), and Tgi represents the glass transition temperature (unit: K) of the homopolymer of monomer i.

[0054] As the Tg of a homopolymer, a value described in a publicly known document is adopted. For example, for the monomers listed below, the following values ​​are used as the Tg of the homopolymer of the monomer. 2-Ethylhexyl acrylate -70℃ n-Hexyl acrylate -65℃ n-Octyl acrylate -65℃ Isononyl acrylate -60℃ n-Nonyl acrylate -58℃ n-Butyl acrylate -55℃ Ethyl acrylate -20℃ Lauryl acrylate 0℃ 2-Ethylhexyl methacrylate -10℃ Methyl acrylate 8℃ n-Butyl methacrylate 20℃ Methyl methacrylate 105℃ Acrylic acid 106℃ Methacrylic acid 228℃ Vinyl acetate 32℃ Styrene 100℃

[0055] For the Tg of homopolymers of monomers other than those exemplified above, the values ​​listed in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999) shall be used. For monomers for which multiple values ​​are listed in this document, the highest value shall be adopted. If the Tg of the homopolymer is not listed in the Polymer Handbook, the value obtained by the measurement method described in JP-A-2007-51271 shall be used.

[0056] (Synthesis of acrylic polymers) The acrylic polymer in the technology disclosed herein is typically obtained by emulsion polymerization of monomer raw materials having the above-mentioned composition. The mode of emulsion polymerization is not particularly limited, and it can be carried out by appropriately adopting various monomer supply methods, polymerization conditions, materials used, etc. similar to those of conventionally known general emulsion polymerization. For example, as the monomer supply method, any of a lump-sum charging method in which all monomer raw materials are supplied to a polymerization vessel at once, a continuous supply (dropping) method, a divided supply (dropping) method, etc. can be adopted. A part or all of the monomer components may be mixed with water and a surfactant in advance to be emulsified, and the emulsion may be supplied to the polymerization vessel. The polymerization temperature can be, for example, about 20°C to 100°C, and is usually appropriate to be about 40°C to 80°C.

[0057] Examples of the polymerization initiator include, but are not limited to, an azo-based initiator, a peroxide-based initiator, a redox-based initiator in which a peroxide and a reducing agent are combined, etc. The polymerization initiator can be used alone or in combination of two or more kinds. Examples of azo initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate, 2,2'-azobis(2-methylpropionamidine)disulfate, 2,2'-azobis(2-methylpropionamidine)dihydrochloride, 2,2'-azobis(2-methylpropionamidine)dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, and 2,2'-azobis(N,N'-dimethyleneisobutylamidine)dihydrochloride. Examples of peroxide initiators include persulfates such as potassium persulfate and ammonium persulfate; benzoyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, dicumyl peroxide, dilauroyl peroxide, di-n-octanoyl peroxide, di(4-methylbenzoyl)peroxide, t-butyl peroxybenzoate, t-butyl peroxyisobutyrate, t-hexyl peroxypivalate, t-butyl peroxypivalate, di(2-ethylhexyl)peroxide, and the like. Examples of peroxydicarbonate include di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, t-butylperoxyneodecanoate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclododecane, 1,1-bis(t-hexylperoxy)cyclohexane, and hydrogen peroxide. Examples of redox initiators include a combination of a peroxide and ascorbic acid (e.g., a combination of hydrogen peroxide and ascorbic acid), a combination of a peroxide and an iron (II) salt (e.g., a combination of hydrogen peroxide and an iron (II) salt), a combination of a persulfate and sodium hydrogen sulfite, and the like.

[0058] The amount of the polymerization initiator used can be appropriately selected depending on the type of the initiator, the type of monomer (composition of the monomer components), the polymerization conditions, etc. The amount of the polymerization initiator used is usually in the range of, for example, about 0.001 to 0.5 parts by weight, preferably 0.002 to 0.3 parts by weight, and more preferably 0.005 to 0.1 parts by weight, relative to 100 parts by weight of the monomer raw material.

[0059] In the emulsion polymerization, various conventionally known chain transfer agents (which may also be understood as molecular weight regulators or polymerization degree regulators) may be used as necessary. The chain transfer agents may be used alone or in combination of two or more. As the chain transfer agent, mercaptans such as n-dodecyl mercaptan, t-dodecyl mercaptan, glycidyl mercaptan, 2-mercaptoethanol, mercaptoacetic acid, thioglycolic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol may be preferably used. When a chain transfer agent is used, the amount of the chain transfer agent used may be, for example, about 0.01 to 1 part by weight, preferably 0.02 to 0.1 parts by weight, and more preferably 0.03 to 0.07 parts by weight, based on 100 parts by weight of the total monomer components. The technology disclosed herein may also be preferably implemented in an embodiment in which no chain transfer agent is used.

[0060] Emulsion polymerization of the monomer raw material is usually carried out in the presence of a surfactant (emulsifier). The amount of the surfactant used is not particularly limited. In consideration of the polymerization stability, the dispersion stability of the polymerization reaction product, and the low contamination of the surface protection sheet, the amount of the surfactant used is usually 0.1 parts by weight or more (e.g., 0.5 parts by weight or more) per 100 parts by weight of the monomer raw material, and 10 parts by weight or less (e.g., 5 parts by weight or less) per 100 parts by weight of the monomer raw material.

[0061] As the surfactant, known anionic surfactants, nonionic surfactants, cationic surfactants, etc. can be used. Usually, anionic or nonionic surfactants are preferred. Surfactants having reactive functional groups (typically radically polymerizable functional groups) may be used. Hereinafter, surfactants having reactive functional groups are referred to as reactive surfactants, whereas general surfactants not having reactive functional groups may be referred to as non-reactive surfactants. The surfactants may be used alone or in combination of two or more.

[0062] Examples of non-reactive anionic surfactants include alkyl sulfates such as lauryl sulfate and octadecyl sulfate; fatty acid salts; alkyl benzene sulfonates such as nonyl benzene sulfonate and dodecyl benzene sulfonate; naphthalene sulfonates such as dodecyl naphthalene sulfonate; alkyl diphenyl ether disulfonates such as dodecyl diphenyl ether disulfonate; polyoxyethylene alkyl ether sulfates such as polyoxyethylene octadecyl ether sulfate and polyoxyethylene lauryl ether sulfate; polyoxyethylene alkyl phenyl ether sulfates such as polyoxyethylene lauryl phenyl ether sulfate; polyoxyethylene styrenated phenyl ether sulfate; sulfosuccinates such as lauryl sulfosuccinate and polyoxyethylene lauryl sulfosuccinate; polyoxyethylene alkyl ether phosphates; polyoxyethylene alkyl ether acetates; etc. When the anionic surfactant forms a salt, the salt may be, for example, a metal salt (preferably a monovalent metal salt) such as sodium salt, potassium salt, calcium salt, magnesium salt, etc., an ammonium salt, an amine salt, etc.

[0063] Examples of non-reactive nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether and polyoxyethylene stearyl ether; polyoxyethylene alkyl phenyl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monostearate, and polyoxyethylene sorbitan monolaurate; polyoxyethylene glyceryl ether fatty acid esters; polyoxyethylene-polyoxypropylene block copolymers; and the like.

[0064] As the reactive surfactant, those having a polymerizable (typically radically polymerizable) functional group can be preferably used. For example, a reactive surfactant having a structure in which a radically polymerizable functional group is introduced into the anionic surfactant or nonionic surfactant as described above can be used. The type of the radically polymerizable functional group is not particularly limited, and can be, for example, an alkenyl group, an acryloyl group, a methacryloyl group, a vinyl group, a vinyl ether group (vinyloxy group), an allyl ether group (allyloxy group), etc. Specific examples of the alkenyl group include a propenyl group and an isopropenyl group (CH2=C(CH3)-). The concept of the propenyl group here includes a 1-propenyl group (CH3-CH=CH-) and a 2-propenyl group (CH2=CH-CH2-; sometimes referred to as an allyl group).

[0065] Examples of anionic reactive surfactants include polyoxyethylene (allyloxymethyl) alkyl ether sulfate (e.g., ammonium salt), polyoxyethylene nonylpropenyl phenyl ether sulfate (e.g., ammonium salt), alkyl aryl sulfosuccinate (e.g., sodium salt), methacryloxy polyoxypropylene sulfate (e.g., sodium salt), polyoxyalkylene alkenyl ether sulfate (e.g., ammonium salt in which the end of the alkenyl group is an isopropenyl group), etc. When anionic reactive surfactants form salts, the salts may be, for example, metal salts such as sodium salts, or nonmetal salts such as ammonium salts or amine salts. Examples of the nonionic reactive surfactant include polyoxyethylene nonylpropenyl phenyl ether.

[0066] Commercially available reactive surfactants include those manufactured by Daiichi Kogyo Seiyaku Co., Ltd. under the trade names "Aqualon HS-05," "Aqualon HS-10," "Aqualon HS-1025," "Aqualon HS-20," "Aqualon KH-10," "Aqualon KH-1025," "Aqualon KH-05," "Aqualon BC-0515," "Aqualon BC-10," "Aqualon BC-1025," "Aqualon BC-20," "Aqualon BC-2020," "Aqualon RN-20," "Aqualon RN-30," and "Aqualon RN-50." Examples of such products include "Aqualon AR-10", "Aqualon AR-20", "Aqualon AR-1025", "Aqualon AR-2020", ADEKA Corporation product names "ADEKA REASOAP SE-10N" and "ADEKA REASOAP SR-1025", Kao Corporation product names "Latemul PD-104", "Latemul PD-420", "Latemul PD-430", and "Latemul PD-450", Sanyo Chemical Industries, Ltd. product names "Eleminol JS-20" and "Eleminol RS-3000", and Nippon Nyukazai Co., Ltd. product name "Anthox MS-60".

[0067] From the viewpoint of emulsification performance and the like, in one embodiment, an anionic reactive surfactant can be preferably used. When a nonionic reactive surfactant is used, more preferable results can be achieved by using it in combination with another surfactant, for example, an anionic reactive surfactant, an anionic non-reactive surfactant, a nonionic non-reactive surfactant, etc.

[0068] By emulsion-polymerizing the monomer raw material in the presence of the reactive surfactant, the reactive surfactant can be reacted and incorporated into the acrylic polymer. The reactive surfactant is incorporated into the acrylic polymer, which reduces the amount of free surfactant, thereby reducing the foaming property. Therefore, performing polymerization using the reactive surfactant can be advantageous for achieving both polymerization stability and low foaming property after polymerization. From the viewpoint of achieving better low foaming property, an embodiment in which only the reactive surfactant is used as the surfactant during emulsion polymerization can be preferably adopted. In addition, the reactive surfactant incorporated into the acrylic polymer is less likely to bleed out to the surface of the adhesive layer because the movement of the reactive surfactant in the adhesive layer is restricted. This is preferable from the viewpoint of improving the low contamination property of the surface protection sheet. In this specification, the term "containing a reactive surfactant" refers to a concept that includes containing the reactive surfactant in a state after its reactive functional group (e.g., radically polymerizable functional group) has reacted. The reactive surfactant in the technology disclosed herein is typically contained in the adhesive composition or the adhesive layer in a form in which at least a part of it is incorporated into the acrylic polymer as described above.

[0069] (tackifier) In the technology disclosed herein, the aqueous dispersion type adhesive composition used to form the adhesive layer contains a tackifier. The use of the tackifier can improve the peel strength (adhesive strength). As the tackifier, one or more types selected from various tackifier resins such as rosin-based resins, rosin derivative resins, petroleum-based resins, terpene-based resins, phenol-based resins, and ketone-based resins can be used.

[0070] The tackifier preferably has a softening point of 100° C. or more, more preferably 140° C. or more, from the viewpoint of increasing the cohesiveness in a high-temperature environment and suppressing a rapid increase in adhesive strength due to heating. Examples of tackifiers having such softening points include "Superester E-865; softening point 160° C.," "Superester E-865NT; softening point 160° C.," "Superester E-650NT; softening point 160° C.," "Tamanol E-100; softening point 150° C.," "Tamanol E-200; softening point 150° C.," "Tamanol 803L; softening point 145 to 160° C.," "Pensel D-160; softening point 150° C.," "Pensel KK; softening point 165° C.," manufactured by Arakawa Chemical Industries Co., Ltd., and "YS Polystar S series," "YS Polystar T series," and "Mighty Ace G series" manufactured by Yasuhara Chemical Co., Ltd., but are not limited thereto. Such tackifiers can be used alone or in combination of two or more. By using a tackifier with a softening point of about 100°C or higher, for example, cohesiveness and other properties (peel strength, edge peel resistance, etc.) can be obtained at a higher level. In some preferred embodiments, the softening point of the tackifier is 120°C or higher, more preferably 130°C or higher, and even more preferably 140°C or higher (e.g., 145°C or higher, or even 150°C or higher).

[0071] The tackifier is typically used by adding it to an aqueous emulsion of an acrylic polymer. The manner of adding the tackifier is not particularly limited, but the tackifier is usually added in the form of an aqueous dispersion (tackifier emulsion) in which the tackifier is dispersed in water. In some preferred embodiments, the tackifier disclosed herein is a tackifier that can be dispersed in water, that is, a so-called aqueous dispersion type tackifier.

[0072] The amount of the tackifier (typically a water-dispersed tackifier) ​​disclosed herein is preferably 5 parts by weight or more relative to 100 parts by weight of the acrylic polymer. By setting the amount of the tackifier to the above lower limit or more, the peel strength (adhesive strength) can be further improved. In some preferred embodiments, the amount of the tackifier (typically a water-dispersed tackifier) ​​is 7 parts by weight or more relative to 100 parts by weight of the acrylic polymer, more preferably 8 parts by weight or more, even more preferably 9 parts by weight or more (for example, 10 parts by weight or more), and may be 20 parts by weight or more, or may be 25 parts by weight or more. The amount of the tackifier (typically a water-dispersed tackifier) ​​disclosed herein is preferably 40 parts by weight or less relative to 100 parts by weight of the acrylic polymer. By setting the amount of the tackifier to the above upper limit or less, the peel strength (adhesive strength) is prevented from increasing excessively, and the non-sticky residue property is easily improved. From this viewpoint, in some preferred embodiments, the amount of the tackifier (typically, a water-dispersible tackifier) ​​used is 30 parts by weight or less, optionally 25 parts by weight or less, optionally 20 parts by weight or less, or optionally 15 parts by weight or less, per 100 parts by weight of the acrylic polymer.

[0073] (Leveling agent) In the technology disclosed herein, the aqueous dispersion type adhesive composition used for forming the adhesive layer contains a leveling agent. The aqueous dispersion type adhesive composition containing a leveling agent can improve the wettability of the aqueous dispersion type adhesive composition to the supporting substrate. By improving the wettability, when the aqueous dispersion type adhesive composition is applied to form an adhesive layer, repelling is less likely to occur in the coating film of the composition. In addition, the thickness of the adhesive layer can be easily reduced (for example, a thickness of 20 μm or less).

[0074] The type of the leveling agent is not particularly limited. Examples of the leveling agent include "Surfynol 420" (acetylene glycol ethylene oxide surfactant, manufactured by Nissin Chemical Industry Co., Ltd.), "Pelex OT-P" (dialkyl sodium sulfosuccinate, manufactured by Kao Corporation), "Neocol P" (dialkyl sodium sulfosuccinate, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), "Neocol SW-C" (dialkyl sodium sulfosuccinate, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), "Nopco Wet 50" (sulfonic acid anionic surfactant, manufactured by San Nopco Co., Ltd.), "SN Wet 126" (modified silicone / special polyether surfactant, manufactured by San Nopco Co., Ltd.), "SN Wet FST2" (nonionic wetting agent of polyoxyalkyleneamine, manufactured by San Nopco Co., Ltd.), "SN Wet S" (nonionic wetting agent of polyoxyalkyleneamine ether, manufactured by San Nopco Co., Ltd.), and "SN Wet 125" (modified silicone surfactant, manufactured by San Nopco Co., Ltd.). The leveling agents can be used alone or in combination of two or more.

[0075] In some preferred embodiments, the leveling agent may be an acetylene glycol ethylene oxide surfactant or sodium dialkyl sulfosuccinate. The leveling agent may further improve the wettability of the aqueous dispersion pressure-sensitive adhesive composition.

[0076] The number of carbon atoms of the sodium dialkyl sulfosuccinate is not particularly limited, but in some embodiments it is 4 or more, preferably 6 or more, and more preferably 8 or more. In addition, the number of carbon atoms of the sodium dialkyl sulfosuccinate is not particularly limited, but in some embodiments it is 20 or less, preferably 12 or less, and more preferably 10 or less.

[0077] In the technology disclosed herein, the amount of the leveling agent used is 0.3 parts by weight or more relative to 100 parts by weight of the acrylic polymer. When the amount of the leveling agent used is the above-mentioned lower limit or more, the wettability of the water-dispersed pressure-sensitive adhesive composition is suitably improved, and therefore, the increase in the repelling property caused by the addition of the tackifier tends to be suppressed. In some preferred embodiments, the amount of the leveling agent used can be 0.4 parts by weight or more relative to 100 parts by weight of the acrylic polymer, more preferably 0.5 parts by weight or more, and may be 0.9 parts by weight or more, or may be 1.5 parts by weight or more. In addition, in the technology disclosed herein, the content of the leveling agent is 3 parts by weight or less relative to 100 parts by weight of the acrylic polymer. By setting the amount of the leveling agent to the above-mentioned upper limit or less, contamination of the adherend can be suppressed. In some embodiments, the amount of the leveling agent used can be 2.5 parts by weight or less relative to 100 parts by weight of the acrylic polymer, and may be 2 parts by weight or less, 1.5 parts by weight or less, 1.2 parts by weight or less, or 0.8 parts by weight or less.

[0078] The amount of the leveling agent used can also be selected based on the relationship with the amount of the tackifier (typically, water-dispersed tackifier) ​​used. Although not particularly limited, the weight ratio (CL / CT) of the leveling agent content (CL) to the tackifier content (CT) in the water-dispersed PSA composition is suitably 0.005 or more, preferably 0.01 or more, and in some embodiments, may be 0.02 or more, 0.03 or more, or 0.04 or more. The weight ratio (CL / CT) of the leveling agent content (CL) to the tackifier content (CT) in the water-dispersed PSA composition is suitably 0.5 or less, preferably 0.4 or less (e.g., 0.3 or less), and in some embodiments, may be 0.2 or less, or may be 0.1 or less.

[0079] (Crosslinking agent) In the technology disclosed herein, a crosslinking agent is used in the adhesive layer. By using a crosslinking agent, the cohesiveness of the adhesive layer can be adjusted so that the adhesive non-remaining property and adhesiveness can be well balanced. In addition, the gel fraction of the adhesive layer can be appropriately adjusted.

[0080] Suitable examples of the crosslinking agent used in the technology disclosed herein include oxazoline-based crosslinking agents, isocyanate-based crosslinking agents, and epoxy-based crosslinking agents. These can be used alone or in combination of two or more. The surface protection sheet obtained using such a crosslinking agent can have a small increase in peel strength and is less likely to leave adhesive residue or stain on the surface of the adherend, even in a usage mode in which the adherend to which the surface protection sheet is attached is stored outdoors for a long period of time.

[0081] As the oxazoline crosslinking agent, those having one or more oxazoline groups in one molecule can be used without any particular limitation. The oxazoline crosslinking agent can be used alone or in combination of two or more. From the viewpoint of use in a water-dispersed pressure-sensitive adhesive composition, the oxazoline crosslinking agent that is soluble or dispersible in water is preferred. The oxazoline group may be any of 2-oxazoline group, 3-oxazoline group, and 4-oxazoline group. Usually, an oxazoline-based crosslinking agent having a 2-oxazoline group can be preferably used. For example, a water-soluble copolymer or a water-dispersible copolymer obtained by copolymerizing an addition polymerizable oxazoline such as 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, or 2-isopropenyl-5-ethyl-2-oxazoline with another monomer can be used as an oxazoline-based crosslinking agent. Commercially available oxazoline-based crosslinking agents include, for example, products manufactured by Nippon Shokubai Co., Ltd. under the trade names "Epocross WS-500," "Epocross WS-700," "Epocross K-2010E," "Epocross K-2020E," and "Epocross K-2030E."

[0082] From the viewpoint of imparting suitable cohesiveness to the pressure-sensitive adhesive layer and obtaining good non-adhesive residue properties, the amount of the oxazoline crosslinking agent used is preferably such that the oxazoline group is 0.1 equivalent or more, preferably 0.15 equivalent or more, more preferably 0.2 equivalent or more, for example 0.3 equivalent or more per equivalent of the carboxyl group contained in the acrylic polymer. Also, from the viewpoint of obtaining good low-staining properties, the amount of the oxazoline crosslinking agent used is preferably such that the oxazoline group is 5 equivalents or less, preferably 3 equivalents or less, more preferably 1 equivalent or less, for example 0.7 equivalents or less (typically 0.5 equivalents or less) per equivalent of the carboxyl group contained in the acrylic polymer.

[0083] As the isocyanate-based crosslinking agent, those having two or more isocyanate groups per molecule can be used without any particular limitation. The isocyanate group in the isocyanate-based crosslinking agent may be an isocyanate group having a protecting group, for example, an isocyanate regenerating functional group (blocked isocyanate) in which the isocyanate group is temporarily protected by a blocking agent treatment or the like. The isocyanate-based crosslinking agent can be used alone or in combination of two or more.

[0084] Examples of the isocyanate crosslinking agent include aromatic polyisocyanates such as tolylene diisocyanate and xylylene diisocyanate; aliphatic isocyanates such as isophorone diisocyanate; alicyclic polyisocyanates such as hexamethylene diisocyanate; and the like. More specifically, for example, lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic polyisocyanates such as dicyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate; aromatic diisocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate and polymethylene polyphenyl diisocyanate; trimethylolpropane / tolylene diisocyanate trimer adducts (such as "Coronate L", a product name of Tosoh Corporation). isocyanate adducts such as trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Tosoh Corporation, product name "Coronate HL", etc.), and isocyanurate of hexamethylene diisocyanate (manufactured by Tosoh Corporation, product name "Coronate HX", etc.); polyisocyanates such as polyether polyisocyanate and polyester polyisocyanate; adducts of these polyisocyanates with polyols; and polyisocyanates obtained by multifunctionalizing these polyisocyanates with isocyanurate bonds, biuret bonds, allophanate bonds, etc.

[0085] From the viewpoint of use in a water-dispersed pressure-sensitive adhesive composition, an isocyanate-based crosslinking agent that is soluble or dispersible in water is preferred. For example, a water-soluble, water-dispersible or self-emulsifying isocyanate-based crosslinking agent can be preferably used. Commercially available products of such isocyanate-based crosslinking agents (aqueous isocyanate-based crosslinking agents) include those manufactured by DIC under the trade names "BURNOCK DNW-5000", "BURNOCK DNW-5010", "BURNOCK DNW-5100", "BURNOCK DNW-5200", "BURNOCK DNW-5500" and "BURNOCK DNW-6000"; those manufactured by Tosoh under the trade names "AQUANATE 100", "AQUANATE 105", "AQUANATE 110", "AQUANATE 120", "AQUANATE 130", "AQUANATE 200" and "AQUANATE 21". Examples include "Takenate WD-220", "Takenate WD-240", "Takenate WD-720", "Takenate WD-725", "Takenate WD-726", "Takenate WD-730", "Takenate WB-700", "Takenate WB-720", and "Takenate WB-920", manufactured by Mitsui Chemicals Polyurethanes; and "Elastron BN-04", "Elastron BN-11", "Elastron BN-27", "Elastron BN-69", and "Elastron BN-77", manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.

[0086] As the epoxy-based crosslinking agent, those having two or more epoxy groups in one molecule can be used without any particular limitation. Epoxy-based crosslinking agents having 3 to 5 epoxy groups in one molecule are preferred. The epoxy-based crosslinking agents can be used alone or in combination of two or more. Epoxy-based crosslinking agents that are soluble or dispersible in water are preferred. Specific examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, and polyglycerol polyglycidyl ether. Commercially available epoxy crosslinking agents include "TETRAD-X" and "TETRAD-C" manufactured by Mitsubishi Gas Chemical Company, Inc., "Epicron CR-5L" manufactured by DIC Corporation, "Denacol EX-512" manufactured by Nagase ChemteX Corporation, and "TEPIC-G" manufactured by Nissan Chemical Industries, Ltd.

[0087] The amount of the crosslinking agent used is not particularly limited, and can be appropriately set so that suitable properties are obtained after crosslinking depending on the copolymerization composition of the acrylic polymer and the type of crosslinking agent used. Although not particularly limited, the amount of the crosslinking agent used relative to 100 parts by weight of the acrylic polymer can be, for example, about 0.01 parts by weight or more (typically about 0.05 parts by weight or more), and may be about 0.1 parts by weight or more, or even about 0.5 parts by weight or more. In addition, from the viewpoint of stability over time of peel strength (adhesive strength stability), etc., the amount of the crosslinking agent used is usually about 15 parts by weight or less (preferably about 10 parts by weight or less, for example about 5 parts by weight or less) relative to 100 parts by weight of the acrylic polymer, and may be about 3 parts by weight or less.

[0088] The adhesive composition may further contain, as necessary, known additives that can be used in aqueous dispersion adhesive compositions, such as viscosity adjusters (thickeners, etc.), release adjusters, plasticizers, softeners, surface lubricants, antistatic agents, preservatives, antifungal agents, and weather resistance improvers (e.g., ultraviolet absorbers, antiaging agents, antioxidants, and light stabilizers), within the range in which the effects of the present invention are not significantly impaired. Each of these additives can be used alone or in combination of two or more. The amount of each additive can be about the same as the amount normally used in the field of adhesive compositions for surface protection sheets.

[0089] The pressure-sensitive adhesive composition may contain, in addition to the acrylic polymer as the base polymer, a polymer other than the acrylic polymer as a secondary polymer, such as a rubber-based polymer, a polyester-based polymer, a urethane-based polymer, or a silicone-based polymer, for the purpose of adjusting the adhesive performance. The secondary polymer is preferably used in an amount of 25 parts by weight or less (more preferably 10 parts by weight or less, for example 5 parts by weight or less) per 100 parts by weight of the acrylic polymer. The technology disclosed herein may also be preferably implemented in an embodiment in which the secondary polymer is not substantially used.

[0090] In the technology disclosed herein, the aqueous dispersion type adhesive composition used for forming the adhesive layer can be prepared, for example, by mixing an aqueous dispersion of an acrylic polymer obtained by emulsion polymerization using a surfactant with a tackifier (typically an aqueous dispersion type tackifier), a leveling agent, a crosslinking agent, and other components used as necessary (for example, additives such as a neutralizing agent and a thickening agent). As the aqueous dispersion, a polymerization reaction liquid obtained by emulsion polymerization, or a polymerization reaction liquid that has been subjected to treatment such as pH adjustment (for example, neutralization), adjustment of non-volatile content, and adjustment of viscosity as necessary can be used. Usually, the dispersion stability of the emulsion can be improved by adding a neutralizing agent such as ammonia water to the polymerization reaction liquid to adjust the pH to an appropriate range (for example, a range of about pH 6 to 9).

[0091] Although not particularly limited, the nonvolatile content (NV) of the pressure-sensitive adhesive composition can be, for example, about 20% by weight or more (typically about 30% by weight or more, and preferably about 40% by weight or more) from the viewpoint of drying efficiency, etc., and can be about 75% by weight or less (typically about 70% by weight or less, and preferably about 60% by weight or less) from the viewpoint of coatability, etc.

[0092] According to this specification, a method for producing a water-dispersed pressure-sensitive adhesive composition is provided, which includes a polymerization step of emulsion-polymerizing a monomer raw material to obtain an aqueous dispersion of an acrylic polymer, and a compounding step of adding a tackifier (typically an aqueous dispersion tackifier), a leveling agent, and a crosslinking agent to the aqueous dispersion. In the polymerization step of obtaining the aqueous dispersion of the acrylic polymer, a surfactant is typically used. As the surfactant, a reactive surfactant can be preferably used. In the compounding step, additives such as a neutralizer and a thickener can be further added as necessary.

[0093] (Formation of adhesive layer) The pressure-sensitive adhesive layer can be formed according to a known pressure-sensitive adhesive layer forming method for pressure-sensitive adhesive sheets. For example, a method (direct method) in which a pressure-sensitive adhesive composition is directly applied (typically coated) to a support substrate and dried to form a pressure-sensitive adhesive layer can be preferably adopted. The pressure-sensitive adhesive layer is typically formed continuously, but may be formed in a regular or random pattern such as a dotted or striped pattern depending on the purpose or use.

[0094] The adhesive composition can be applied using a known or conventional coater such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a comma coater, a dip roll coater, a die coater, a bar coater, a knife coater, or a spray coater. Alternatively, the adhesive composition may be applied by impregnation or a curtain coating method. From the viewpoint of promoting the crosslinking reaction and improving the production efficiency, the adhesive composition is preferably dried under heating. The drying temperature can be, for example, about 40°C to 150°C, and is usually preferably about 50°C to 130°C (for example, 60°C to 100°C). After drying the adhesive composition, aging may be performed for the purpose of adjusting the component migration in the adhesive layer, advancing the crosslinking reaction, and relaxing distortion that may exist in the support substrate or the adhesive layer.

[0095] The thickness of the adhesive layer is not particularly limited, and may be, for example, about 1 μm to 100 μm. From the viewpoint of suppressing an increase in peel strength (adhesive strength) and non-adhesive residue, the thickness of the adhesive layer is usually 30 μm or less, preferably 25 μm or less, and more preferably 20 μm or less. The technology disclosed herein can be suitably implemented in the form of a surface protection sheet in which the thickness of the adhesive layer is 17 μm or less (typically 15 μm or less), and further 14 μm or less. When the thickness of the adhesive layer is small, the coating thickness of the water-dispersible adhesive composition also becomes small, and coating defects that cause appearance defects of the adhesive layer, such as streaks and repelling caused by air bubbles or aggregates, tend to occur easily. Therefore, it is particularly meaningful to apply the technology disclosed herein to prevent such coating defects. From the viewpoint of adhesion to the surface of the adherend, the thickness of the pressure-sensitive adhesive layer is usually 1 μm or more, preferably 2 μm or more (e.g., 3 μm or more), more preferably 4 μm or more (e.g., 5 μm or more), and even more preferably 6 μm or more. The technology disclosed herein can be preferably implemented in the form of a surface protection sheet having a pressure-sensitive adhesive layer having a thickness of 2 μm or more and 20 μm or less (e.g., 6 μm or more and 14 μm or less).

[0096] <Surface protection sheet> The thickness of the surface protection sheet disclosed herein can be, for example, 300 μm or less, and from the viewpoint of the handling property of the surface protection sheet, it is usually appropriate to be 225 μm or less, and it is preferably 175 μm or less (for example, 125 μm or less), and it may be 100 μm or less. In one embodiment, the thickness of the surface protection sheet can be 85 μm or less, and it may be 70 μm or less, 65 μm or less, or 56 μm or less. From the viewpoint of strength and protection, the thickness of the surface protection sheet is usually appropriate to be 12 μm or more, and it is preferably 20 μm or more (for example, more than 20 μm), and it may be 30 μm or more, 40 μm or more, or 44 μm or more.

[0097] Although not particularly limited, the adhesive layer of the surface protection sheet disclosed herein preferably has a gel fraction of 60% by weight or more, preferably 70% by weight or more from the viewpoint of obtaining good non-stickiness, and more preferably 80% by weight or more. The gel fraction of the adhesive layer is typically 99.9% by weight or less, and preferably 99% by weight or less from the viewpoint of adhesion to the adherend, more preferably 95% by weight or more, and may be 90% by weight or less, or may be less than 90% by weight. A surface protection sheet having an adhesive layer with such a gel fraction is preferable because it is easy to achieve a good balance between good adhesive strength suitable for protecting the adherend and good cohesive strength suitable for re-peeling from the adherend. The gel fraction of the adhesive layer can be adjusted, for example, by the copolymerization composition of the acrylic polymer, the selection of the type and amount of the crosslinking agent, the selection of the type and amount of the surfactant, the use or non-use of a chain transfer agent and the amount of the chain transfer agent used, etc. In principle, the upper limit of the gel fraction is 100% by weight.

[0098] Here, the gel fraction of the adhesive layer is determined by wrapping a measurement sample with a weight W1 in a porous sheet made of tetrafluoroethylene resin and immersing it in ethyl acetate at room temperature for one week, then drying the measurement sample and measuring the weight W2 of the portion insoluble in ethyl acetate, and substituting W1 and W2 into the following formula: gel fraction [%] = W2 / W1 × 100. More specifically, the gel fraction can be measured by the following method. That is, about 0.1 g of the measurement sample is wrapped in a purse-like shape with a porous tetrafluoroethylene resin sheet having an average pore size of 0.2 μm, and the opening is tied with a kite string. The total weight Wa (mg) of the porous tetrafluoroethylene resin sheet and the kite string is measured in advance. Then, the weight of the package (total weight of the adhesive layer and the package) Wb (mg) is measured. The package is placed in a screw tube with a capacity of 50 mL (one screw tube is used for one package), and the screw tube is filled with ethyl acetate. After leaving it at room temperature (typically 23° C.) for 7 days, the package is taken out and dried at 120° C. for 2 hours, and the weight Wc (mg) of the package after drying is measured. The gel fraction (%) of the adhesive layer is calculated by the following formula: Gel fraction (%) = (Wc-Wa) / (Wb-Wa) x 100 As the tetrafluoroethylene resin porous sheet, a product named "Nitoflon (registered trademark) NTF1122" manufactured by Nitto Denko Corporation or an equivalent product can be used.

[0099] Although not particularly limited, the pressure-sensitive adhesive layer of the surface protection sheet disclosed herein has a weight average molecular weight (Mw) of the ethyl acetate soluble portion (sol portion) of 3×10 5 ~3×10 6 Preferably, 5×10 5 ~2.5×10 6 It is more preferable that the Mw of the sol component is 3×10 5 If the Mw of the sol is smaller than 3×10, the adhesive layer will have insufficient cohesion, and adhesive residue and increased peel strength may occur. 6 If it is too large, the adhesion to the adherend surface tends to decrease.

[0100] Here, the Mw of the sol fraction refers to the weight average molecular weight based on standard polystyrene obtained by performing gel permeation chromatography (GPC) on a measurement sample (typically the above sol fraction). Specifically, the Mw of the sol fraction is measured by the following method.

[0101] [Weight average molecular weight (Mw) measurement method] The adhesive is immersed in ethyl acetate and left to soak at room temperature for 7 days to elute the soluble matter, and the extract of the soluble matter is dried to obtain a measurement sample. The measurement sample may be obtained, for example, by drying the polymer dissolved in ethyl acetate during the above-mentioned gel fraction measurement at room temperature. This measurement sample is redissolved in tetrahydrofuran (THF) to prepare a 0.1 wt % THF solution. This THF solution is filtered through a membrane filter with an average pore size of 0.45 μm to obtain a filtrate (sample solution for molecular weight measurement), and the Mw is determined based on standard polystyrene using a GPC measurement device. As the GPC measurement device, it is recommended to use a model named "HLC-8320GPC" manufactured by Tosoh Corporation. The measurement conditions are as follows. [GPC measurement conditions] Column: TSKgel GMH-H(S) x 2 Column size: 7.8mm I.D. x 300mm Detector: Differential refractometer Eluent:THF Flow rate: 0.5mL / min Measurement temperature: 40℃ Sample injection volume: 100 μL

[0102] In some preferred embodiments, the surface protection sheet has a peel strength (adhesive strength) S measured against a stainless steel plate (SUS plate) at a tensile speed of 10 mm / min and a peel angle of 180 degrees. A The peel strength S is 1.3 N / 20 mm or more. When a surface protection sheet is attached to an adherend and the adherend is subjected to a process involving three-dimensional deformation, such as press processing, a surface protection sheet that cannot maintain close contact with the deformed adherend tends to lift or peel off at a relatively slow speed. For this reason, the peel strength S, which is measured by peeling at a tensile speed of 10 mm / min, which is slower than the usual measurement conditions, is A A surface protection sheet having a peel strength S of at least the above lower limit is unlikely to peel off or float from an adherend, even when used for protecting the surface of a metal plate during metal plate processing such as press working. A The peel strength S measured at a tensile speed of 10 mm / min may be 1.4 N / 20 mm or more, or 1.5 N / 20 mm or more. A is suitably 10.0N / 20mm or less, may be 8.0N / 20mm or less, 7.0N / 20mm or less, 6.0N / 20mm or less, 5.0N / 20mm or less, or 4.0N / 20mm or less. A Specifically, it can be measured by the method described in the Examples below.

[0103] The adhesive strength (initial adhesive strength) S of the surface protection sheet disclosed herein is measured under the conditions of a pulling speed of 0.3 m / min and a peel angle of 180 degrees after being attached to a SUS plate and held at 23°C for 30 minutes. B is not particularly limited. In some embodiments, the initial adhesive strength S B is 1.0 N / 20 mm or more, preferably 2.0 N / 20 mm or more, and more preferably 3.0 N / 20 mm or more. B may be 4.0N / 20mm or more, 5.0N / 20mm or more, or 6.0N / 20mm or more. In addition, the initial adhesive strength S B The initial adhesive strength S may be, for example, 15 N / 20 mm or less, and is preferably 10 N / 20 mm or less, more preferably, for example, 8.0 N / 20 mm or less, from the viewpoint of reworkability (ease of repositioning) when attaching the surface protection sheet. B The initial adhesion strength S disclosed herein may be 8.0 N / 20 mm or less, 7.0 N / 20 mm or less, or even 5.0 N / 20 mm or less (e.g., 4.0 N / 20 mm or less). B Specifically, it can be measured by the method described in the Examples below.

[0104] The adhesive strength (post-heat adhesive strength) S of the surface protection sheet disclosed herein is measured under the conditions of a pulling speed of 0.3 m / min and a peel angle of 180 degrees after being attached to a SUS plate and held at 100°C for 1 hour. C is not particularly limited. In some embodiments, the post-heat adhesive strength S C is 1.0 N / 20 mm or more, preferably 2.0 N / 20 mm or more, and more preferably 3.0 N / 20 mm or more. C The adhesive strength after heating S may be 4.0N / 20mm or more, 5.0N / 20mm or more, or 6.0N / 20mm or more. CThe adhesive strength after heating S can be, for example, 15 N / 20 mm or less, and is preferably 12 N / 20 mm or less, more preferably, for example, 10 N / 20 mm or less, from the viewpoint of reworkability (repositionability) when attaching the surface protection sheet. C The post-heat adhesive strength S disclosed herein may be 8.0 N / 20 mm or less, 7.0 N / 20 mm or less, or even 5.0 N / 20 mm or less (e.g., 4.0 N / 20 mm or less). C Specifically, it can be measured by the method described in the Examples below.

[0105] In some preferred embodiments, the surface protection sheet has a post-heat adhesive strength change rate (S C / S B ) is about 1.5 or less. According to the surface protection sheet in which the increase in adhesive strength due to heating is suppressed, even if the surface protection sheet is heated in a state attached to an adherend, an excessive increase in adhesive strength is suppressed, and the non-adhesive residue property is easily improved. In one embodiment, the adhesive strength change rate after heating may be about 1.4 or less, or may be about 1.3 or less. The lower limit of the adhesive strength change rate after heating is not particularly limited, but may be about 0.8 or more, or may be about 0.9 or more, from the viewpoint of balancing with other adhesive properties.

[0106] The rate of change in adhesive strength after heating is measured by attaching the tape to a SUS plate, holding it at 23°C for 30 minutes, and then measuring the adhesive strength (initial adhesive strength) S at a pulling speed of 0.3 m / min and a peel angle of 180 degrees. B The adhesive strength (adhesive strength after heating) S is measured under the conditions of a pulling speed of 0.3 m / min and a peel angle of 180 degrees after attaching the adhesive to a SUS plate and holding it at 100°C for 1 hour. C Based on the above, the adhesive strength after heating is S C The initial adhesive strength S B It can be calculated by dividing by .

[0107] In a preferred embodiment, the surface protection sheet is transparent (including translucent). Such a surface protection sheet can be preferably used, for example, in an embodiment including performing an appearance inspection of the adherend surface while the sheet is attached to the adherend. The surface protection sheet disclosed herein has excellent appearance quality (for example, few appearance defects such as dents and streaks that may be confused with defects on the adherend surface), and can contribute to improving the inspection accuracy in a usage embodiment in which an appearance inspection of the adherend surface is performed through the surface protection sheet. Specifically, the surface protection sheet can exhibit a total light transmittance of 50% or more. In addition, the haze value of the surface protection sheet is preferably 30% or less (for example, 20% or less).

[0108] In addition, the pressure applied to the adherend when the surface protection sheet is attached or the state of being attached to the adherend continues for a long time may cause defects such as recesses on the surface (adhesive surface) of the pressure-sensitive adhesive layer of the surface protection sheet to deform the surface shape of the adherend. The surface protection sheet disclosed herein tends to have excellent smoothness of the pressure-sensitive adhesive layer surface by suppressing recesses on the surface of the pressure-sensitive adhesive layer caused by repelling of the water-dispersed pressure-sensitive adhesive composition. Therefore, the surface (adherend surface) to which the surface protection sheet is attached may be less likely to deform.

[0109] The matters disclosed by this specification include the following: [1] A pressure-sensitive adhesive layer formed from a water-dispersed pressure-sensitive adhesive composition containing an acrylic polymer, a water-dispersed tackifier, a leveling agent, and a crosslinking agent; A surface protection sheet comprising: a support substrate in a sheet shape having a first surface and a second surface, the support substrate supporting the pressure-sensitive adhesive layer on the first surface, the content of the water-dispersible tackifier is 5 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the acrylic polymer, The surface protection sheet, wherein the content of the leveling agent is 0.3 parts by weight or more and 3 parts by weight or less based on 100 parts by weight of the acrylic polymer. [2] The surface protection sheet according to [1], wherein at least the first surface of the supporting substrate is made of a polyolefin resin. [3] The surface protection sheet according to the above-mentioned [1] or [2], wherein the water-dispersible tackifier comprises a tackifier having a softening point of 100° C. or higher (preferably 140° C. or higher). [4] The surface protection sheet according to any one of [1] to [3] above, wherein the leveling agent comprises an acetylene glycol ethylene oxide-based surfactant or a sodium dialkyl sulfosuccinate. [5] Peel strength S measured against stainless steel plate at a tensile speed of 10 mm / min and a peel angle of 180 degrees A The surface protection sheet according to any one of the above [1] to [4], wherein the compressive strength is 1.3 N / 20 mm or more and 10.0 N / 20 mm or less. [6] The surface protection sheet according to any one of the above [1] to [5], having a thickness of more than 20 μm and not more than 100 μm (preferably 44 μm or more and 56 μm or less). [7] The surface protection sheet according to any one of the above [1] to [6], wherein the pressure-sensitive adhesive layer has a thickness of 2 μm or more and 20 μm or less (preferably 6 μm or more and 14 μm or less). [8] The surface protection sheet according to any one of the above [1] to [7], wherein the pressure-sensitive adhesive layer is crosslinked with at least one crosslinking agent selected from the group consisting of an epoxy-based crosslinking agent, an isocyanate-based crosslinking agent, an oxazoline-based crosslinking agent, an aziridine-based crosslinking agent, a carbodiimide-based crosslinking agent, a melamine-based crosslinking agent, a peroxide-based crosslinking agent, a urea-based crosslinking agent, a metal alkoxide-based crosslinking agent, a metal chelate-based crosslinking agent, a metal salt-based crosslinking agent, a hydrazine-based crosslinking agent, an amine-based crosslinking agent, and a silane coupling agent. [9] Preparing a water-dispersed pressure-sensitive adhesive composition containing an acrylic polymer, a water-dispersed tackifier, a leveling agent, and a crosslinking agent; and directly applying the aqueous PSA composition to the first surface of a sheet-shaped supporting substrate having a first surface and a second surface to form a PSA layer, wherein the content of the water-dispersible tackifier is 5 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the acrylic polymer, The content of the leveling agent is 0.3 parts by weight or more and 3 parts by weight or less based on 100 parts by weight of the acrylic polymer. A method for manufacturing a surface protection sheet.

[10] A water-dispersible PSA composition comprising an acrylic polymer, a water-dispersible tackifier, a leveling agent, and a crosslinking agent, the content of the water-dispersible tackifier is 5 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the acrylic polymer, The water-dispersible pressure-sensitive adhesive composition for surface protective sheets, wherein the content of the leveling agent is 0.3 parts by weight or more and 3 parts by weight or less based on 100 parts by weight of the acrylic polymer.

[11] The water-dispersible pressure-sensitive adhesive composition according to

[10] above, wherein the acrylic polymer is an acrylic polymer having a monomer composition containing from about 40% by weight to about 99.9% by weight of an alkyl acrylate having an alkyl group with 4 to 9 carbon atoms.

[12] The aqueous dispersion pressure-sensitive adhesive composition according to the above-mentioned

[10] or

[11] , wherein the aqueous dispersion pressure-sensitive adhesive composition contains a tackifier having a softening point of 100° C. or higher (preferably 140° C. or higher).

[13] The water-dispersed pressure-sensitive adhesive composition according to any one of the above

[10] to

[12] , comprising an acetylene glycol ethylene oxide surfactant or a sodium dialkylsulfosuccinate as the leveling agent.

[14] The aqueous dispersion pressure-sensitive adhesive composition according to any one of the above

[10] to

[13] , comprising, as the crosslinking agent, at least one crosslinking agent selected from the group consisting of an epoxy-based crosslinking agent, an isocyanate-based crosslinking agent, an oxazoline-based crosslinking agent, an aziridine-based crosslinking agent, a carbodiimide-based crosslinking agent, a melamine-based crosslinking agent, a peroxide-based crosslinking agent, a urea-based crosslinking agent, a metal alkoxide-based crosslinking agent, a metal chelate-based crosslinking agent, a metal salt-based crosslinking agent, a hydrazine-based crosslinking agent, an amine-based crosslinking agent, and a silane coupling agent. EXAMPLES

[0110] Below, some experimental examples related to the present invention will be described, but it is not intended that the present invention be limited to those specific examples. In the following description, "parts" and "%" are based on weight unless otherwise specified. In addition, unless otherwise specified, the amount of each material used is based on the amount of active ingredient.

[0111] <Preparation of Water-Dispersed Pressure-Sensitive Adhesive Composition> Example 1 A monomer raw material consisting of 58 parts of n-butyl acrylate (BA), 40 parts of n-butyl methacrylate (BMA), and 2 parts of acrylic acid (AA) was mixed with 2 parts of a surfactant (Aqualon BC-2020, a product name of Daiichi Kogyo Seiyaku Co., Ltd., polyoxyethylene-1-(allyloxymethyl) alkyl ether ammonium sulfate with an EO addition mole number of 30 or less) and 150 parts of water, and an emulsion of the monomer raw material was prepared by emulsifying the mixture in an emulsifier (homomixer) while introducing nitrogen gas. The above emulsion was placed in a reaction vessel equipped with a thermometer, a nitrogen gas inlet tube, a cooler, and a stirrer, and heated to a liquid temperature of 50°C while stirring under a nitrogen stream. 0.03 parts of 2,2'-azobis(2-methylpropionamidine)dihydrochloride (manufactured by Wako Pure Chemical Industries, Ltd., product name "V-50") was added as a polymerization initiator, and the liquid temperature was kept at around 50°C to carry out a polymerization reaction for 5 hours. Ammonia water was added to the obtained polymerization reaction liquid to adjust the pH to about 8. In this way, an aqueous dispersion of an acrylic polymer was prepared. To this aqueous dispersion, 1.5 parts of a crosslinker (an oxazoline-based crosslinker manufactured by Nippon Shokubai Co., Ltd., product name "Epocross WS-500"), 10 parts of a tackifier Tf1 (terpene phenol, product name "Tamanol E-200NT"), and 0.5 parts of a leveling agent (product name "Surfynol 420") were mixed per 100 parts of the non-volatile matter contained in the aqueous dispersion to prepare the adhesive composition of this example. This adhesive composition was applied with a bar coater to the corona-treated surface (first surface) of a 40 μm-thick polyethylene film, one side of which had been corona-discharge-treated, so that the thickness after drying would be 10 μm. This was dried at 70° C. for 2 minutes and then aged at 50° C. for 1 day to produce an adhesive sheet according to this example.

[0112] (Examples 2 and 3) A pressure-sensitive adhesive sheet according to this example was produced in the same manner as in Example 1, except that the amount of tackifier Tf1 used was changed as shown in Table 1.

[0113] Example 4 A pressure-sensitive adhesive sheet according to this example was produced in the same manner as in Example 1, except that the amount of the leveling agent used was changed as shown in Table 1.

[0114] Example 5 An adhesive sheet according to this example was produced in the same manner as in Example 1, except that tackifier Tf2 (special rosin ester, product name "Super Ester E-865NT") was used instead of tackifier Tf1.

[0115] Example 6 An aqueous dispersion of an acrylic polymer of this example was prepared in the same manner as in Example 1, except that the monomer raw material was changed to a monomer raw material consisting of 58 parts of 2-ethylhexyl acrylate (2EHA), 40 parts of n-butyl methacrylate (BMA), and 2 parts of acrylic acid (AA). 2.5 parts of a crosslinker (an oxazoline crosslinker manufactured by Nippon Shokubai Co., Ltd., product name "Epocross WS-500"), 25 parts of a tackifier Tf1 (terpene phenol, product name "Tamanol E-200NT"), and 0.5 parts of a leveling agent (product name "Surfynol 420") were mixed with this aqueous dispersion relative to 100 parts of nonvolatile matter contained in the aqueous dispersion to prepare an adhesive composition according to this example. An adhesive sheet according to this example was produced in the same manner as in Example 1, except that this adhesive composition was used.

[0116] Comparative Example 1 An adhesive sheet according to this example was produced in the same manner as in Example 1, except that tackifier Tf1 was not used.

[0117] (Comparative Examples 2 and 3) A pressure-sensitive adhesive sheet according to this example was produced in the same manner as in Example 1, except that the amount of tackifier Tf1 used was changed as shown in Table 1.

[0118] Comparative Example 4 The pressure-sensitive adhesive sheet according to this example was produced in the same manner as in Example 1, except that no leveling agent was used.

[0119] Comparative Example 5 The pressure-sensitive adhesive sheet according to this example was produced in the same manner as in Example 3, except that no leveling agent was used.

[0120] (Comparative Examples 6 and 7) A pressure-sensitive adhesive sheet according to this example was produced in the same manner as in Example 1, except that the amount of the leveling agent used was changed as shown in Table 1.

[0121] An overview of each example is shown in Table 1. In Table 1, "-" indicates non-use.

[0122] <Measurement and Evaluation> (Adhesive strength change rate after heating S C / S B ) First, the initial adhesive strength S of the adhesive sheet according to each example was measured by the following method. B was measured. The adhesive sheet according to each example was cut into a strip of 20 mm width and 100 mm length to prepare a test piece. The adhesive surface of the test piece was pressed onto a stainless steel plate (SUS430BA plate) as an adherend using a laminator at a pressure of 0.26 MPa. The sample was left for 30 minutes in a standard environment of 23°C x 50% RH, and then, under the standard environment, a universal tensile tester was used to measure the peel strength (initial adhesive strength) S at a tensile speed of 0.3 m / min and a peel angle of 180 degrees. B [N / 20mm] was measured.

[0123] Next, the post-heat adhesive strength S of the pressure-sensitive adhesive sheet according to each example was measured by the following method. C was measured. The pressure-sensitive adhesive sheet according to each example was cut into a strip of 20 mm width and 100 mm length to prepare a test piece. The adhesive surface of the test piece was pressed onto a stainless steel plate (SUS430BA plate) as an adherend using a laminator at a pressure of 0.26 MPa. After keeping the sample in an environment of 100°C for 1 hour, the peel strength (adhesive strength after heating) S was measured using a universal tensile tester under the standard environment of 23°C x 50% RH at a tensile speed of 0.3 m / min and a peel angle of 180°. C [N / 20mm] was measured.

[0124] The adhesive strength after heating S obtained for each example of the pressure-sensitive adhesive sheet C The initial adhesive strength S B By dividing by this, the adhesive strength change rate after heating (S C / S B The results are shown in Table 1.

[0125] (Adhesive strength S A ) The pressure-sensitive adhesive sheet according to each example was cut into a rectangular shape measuring 20 mm in width and 80 mm in length to prepare a test piece. A stainless steel plate SUS430BA was used as the adherend. The adhesive surface of the test piece was pressed onto the surface of the adherend using an automatic pressing device specified in JIS Z0237. After leaving the sample for 30 minutes under standard conditions of 23°C and 50% RH, the peel strength (adhesive strength) S was measured using a universal tensile tester under the standard conditions of a tensile speed of 10 mm / min and a peel angle of 180°. A The results are shown in Table 1.

[0126] (Coatability) The coating property of the adhesive composition was evaluated as follows, using the corona discharge-treated surface of the support substrate. That is, the adhesive composition prepared in each example was coated on the corona discharge-treated surface of the support substrate used in the example with a Baker-type applicator so that the width was 20 cm, the length was 30 cm, and the thickness after drying was 10 μm. This was dried at 80° C. for 5 minutes to form an adhesive layer. The above coating was performed within 3 hours after the preparation of the adhesive composition. The obtained adhesive layer was visually observed, and the coating property was evaluated according to the following three levels. The results are shown in Table 1. E: No repelling was observed on either the outer edge or the inside of the adhesive layer (excellent coatability). G: Capping is observed only on the outer edge of the adhesive layer, or 5 or less cappings are observed inside the adhesive layer (has sufficient coating properties for practical use). P: Repelling is observed in more than five places inside the adhesive layer (poor coatability).

[0127] (processability) The adhesive sheet according to each example was cut into a square shape of 100 mm long x 100 mm wide to prepare a test piece. The test piece was attached to one side of a stainless steel plate (SUS304BA) having a thickness of 0.4 mm, and a press machine (AIDA 60t press machine) was used to press a jig toward the stainless steel plate from the side where the adhesive sheet was attached, to obtain a lunchbox-shaped press molded body (specifically, a molded body in a state where the adhesive sheet was attached to the surface of the stainless steel plate; the same applies below) of a 40 mm square tube with a folded side of 15 mm long on the periphery and a drawing depth of 15 mm. The obtained molded body was left for one day in an environment of 23°C and 50% RH, and then the appearance of the molded body was visually observed to confirm the presence or absence of tearing or peeling of the adhesive sheet attached to the molded body. Based on the results, the processability of the adhesive sheet was evaluated according to the following three levels. The results are shown in Table 1. E: None of the following occurred: tearing of the adhesive sheet, lifting or peeling of the adhesive sheet at the square tube portion, dents, or lifting or peeling of the adhesive sheet at the peripheral portion (excellent processability). G: There was no tearing of the adhesive sheet, no lifting or peeling of the adhesive sheet in the square tube portion, and no dents, but there was lifting or peeling of the adhesive sheet in the peripheral portion (sufficient processability for practical use). P: At least one of the following occurred: tearing of the adhesive sheet, lifting or peeling of the adhesive sheet at the rectangular tube portion, and dents (poor processability).

[0128] (Low pollution) Using the same method as in the evaluation of processability above, a press molded product was obtained with the adhesive sheet attached to the surface of a stainless steel plate, and the molded product was left for 7 days in an environment of 23°C and 50% RH, after which the adhesive sheet was peeled off and removed by hand from the surface of the molded product. The surface of the molded product after the adhesive sheet was removed was visually observed, and the anti-staining properties of the adhesive sheet were evaluated according to the following two levels. The results are shown in Table 1. G: No glue residue or discoloration is observed (excellent low contamination). P: Glue residue or discoloration is observed (poor stain-resistant properties).

[0129] In the low-staining evaluation, adhesive residue was observed on the surface of the molded product of Comparative Example 3, and the surfaces of the molded products of Comparative Examples 6 and 7 were colored white.

[0130] [Table 1]

[0131] As shown in Table 1, Examples 1 to 6, which contain a tackifier and a leveling agent in the respective ranges, provide pressure-sensitive adhesive sheets with excellent adhesive strength, improved coatability (a property suitable for suppressing defects in the appearance of the pressure-sensitive adhesive sheet) and low staining properties for adherends. In addition, the adhesive strength (particularly the adhesive strength S measured at a peel speed of 10 mm / min) was A It was confirmed that pressure-sensitive adhesive sheets with a high adhesive strength change rate S tend to have excellent processability (the property of being able to withstand press processing and suppress peeling, lifting, etc.). C / S BIt was confirmed that the adhesive strength was approximately 1.3 or less, and no rapid increase in adhesive strength was observed even when heated at 100° C. for 1 hour. Since an excessive increase in adhesive strength can cause adhesive residue to be left on the adherend surface when the adhesive sheet is peeled off, the adhesive sheets of Examples 1 to 6 tend to favorably suppress the occurrence of adhesive residue even when heated, that is, they tend to maintain low contamination even when heated.

[0132] On the other hand, it was confirmed that the adhesive sheet of Comparative Example 1, which did not use a tackifier, and the adhesive sheet of Comparative Example 2, which contained 4 parts by weight of the tackifier relative to 100 parts by weight of the acrylic polymer, had lower adhesive strength and reduced processability compared to Examples 1 to 6. It was also confirmed that the adhesive sheet of Comparative Example 3, which contained 50 parts by weight of the tackifier relative to 100 parts by weight of the acrylic polymer, tended to leave adhesive residue on the adherend after peeling, and to deteriorate the contamination. The adhesive sheets of Comparative Examples 4 and 5, which did not use a leveling agent, showed inferior coating properties compared to Examples 1 to 6. The adhesive sheets of Comparative Examples 6 and 7, which contained 5 parts by weight or 10 parts by weight of the leveling agent relative to 100 parts by weight of the acrylic polymer, tended to have lower adhesive strength and deteriorated processability. It was also confirmed by comparing Comparative Examples 6 and 7 with Examples 1 to 6 that when the content of the leveling agent was higher than the specified range, contamination was likely to occur on the adherend surface after peeling.

[0133] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]

[0134] 1: Supporting base material 1A: First side (front) 1B: Second side (back) 2: Adhesive layer 2A: Adhesive surface 10: Surface protection sheet

Claims

1. a pressure-sensitive adhesive layer formed from a water-dispersed pressure-sensitive adhesive composition containing an acrylic polymer, a water-dispersed tackifier, a leveling agent, and a crosslinking agent; A surface protection sheet comprising: a support substrate having a sheet shape having a first surface and a second surface, the support substrate supporting the pressure-sensitive adhesive layer on the first surface, The content of the water-dispersible tackifier is 5 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the acrylic polymer, The content of the leveling agent is 0.3 parts by weight or more and 3 parts by weight or less with respect to 100 parts by weight of the acrylic polymer.

2. The surface protection sheet according to claim 1 , wherein at least the first surface of the supporting substrate is made of a polyolefin resin.

3. The peel strength S measured against a stainless steel plate at a tensile speed of 10 mm / min and a peel angle of 180 degrees A The surface protection sheet according to claim 1 or 2, wherein the strength is 1.3 N / 20 mm or more and 10.0 N / 20 mm or less.

4. The surface protective sheet according to claim 1 or 2, having a thickness of more than 20 μm and not more than 100 μm.

5. The surface protective sheet according to claim 1 or 2, wherein the pressure-sensitive adhesive layer has a thickness of 2 μm or more and 20 μm or less.

6. Preparing a water-dispersed PSA composition containing an acrylic polymer, a water-dispersed tackifier, a leveling agent, and a crosslinking agent; and directly applying the aqueous PSA composition to a first surface of a sheet-shaped supporting substrate having a first surface and a second surface to form a PSA layer, the content of the water-dispersible tackifier is 5 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the acrylic polymer, The content of the leveling agent is 0.3 parts by weight or more and 3 parts by weight or less based on 100 parts by weight of the acrylic polymer. A method for manufacturing a surface protection sheet.

Citation Information

Patent Citations

  • Surface protection sheet

    JP2018016677A